The power spectrum of the Lyman-α clouds - Amendola, Luca; Savaglio, Sandra (Arxiv, 1999)
We investigate the clustering properties of 13 QSO lines of sight in flat space, with average redshifts from z~2 to 4. We estimate the 1-D power spectrum and the integral density of neighbours, and discuss their variation with respect to redshift and column density. We compare the results with standard CDM models, and estimate the power spectrum of Lyman-alpha clustering as a function both of redshift and column density. We find that a) there is no significant periodicity or characteristic scale; b) the clustering depends both on column density and redshift; c) the clustering increases linearly only if at the same time the HI column density decreases strongly with redshift. The results remain qualitatively the same assuming an open cosmological model.